2021
DOI: 10.1186/s12974-021-02325-6
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated phosphoinositide 3-kinase signaling in microglia: shaping chronic neuroinflammation

Abstract: Microglia are integral mediators of innate immunity within the mammalian central nervous system. Typical microglial responses are transient, intending to restore homeostasis by orchestrating the removal of pathogens and debris and the regeneration of damaged neurons. However, prolonged and persistent microglial activation can drive chronic neuroinflammation and is associated with neurodegenerative disease. Recent evidence has revealed that abnormalities in microglial signaling pathways involving phosphatidylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 187 publications
(151 reference statements)
0
47
0
Order By: Relevance
“…The over-opening of mPTP produces excessive ROS, leading to the damage of neuron, microglia and blood vessels [ 42 , 43 ]. Therefore, inhibition of over-opening of mPTP will alleviate cerebral ischemia/reperfusion injury [ 44 ]. In vitro experimental results indicated that as compared with free CsA, CsA@HFn significantly reduced the over-opening of mPTP, mitochondrial damage and ROS content in OGD/R injured SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The over-opening of mPTP produces excessive ROS, leading to the damage of neuron, microglia and blood vessels [ 42 , 43 ]. Therefore, inhibition of over-opening of mPTP will alleviate cerebral ischemia/reperfusion injury [ 44 ]. In vitro experimental results indicated that as compared with free CsA, CsA@HFn significantly reduced the over-opening of mPTP, mitochondrial damage and ROS content in OGD/R injured SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia is immune effector cells inherent in the central nervous system, and it distributed in gray matter and white matter [ 44 ]. Microglia makes up about 10% of the total number of brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, plenty of new drugs, such as luteolin ( Luo et al, 2019 ), ginsenoside Rg1 ( Chen et al, 2019a ), and baicalein ( Yang et al, 2019 ) were also found to play a neuroprotective role by targeting the PI3K-Akt signaling pathway after ischemic stroke. Erskine Chu et al summarized that dysregulated PI3K-AKT signaling in microglia could shape chronic neuroinflammation, and put forward the view that pharmacological manipulation of the PI3K-AKT signaling axis can yield neuroprotective effects based on various studies ( Chu et al, 2021 ). In addition, other top immune genes are IL6 and TNF, which are also important immunoinflammatory molecules that participated in ischemic stroke ( Chen et al, 2019b ; Jenny et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The chronicization of neuroinflammation results in strong changes in the inflammatory profile of microglia, as a consequence of a continuous release of neurotoxic inflammatory mediators, such as inducible nitric oxide synthase (iNOS) and pro-inflammatory cytokines, including IL-1 and tumor necrosis factor TNF-α, clinically resulting in an increased predisposition to the development of cognitive impairment and therefore also associated mood disorders, such as depression [ 43 ].…”
Section: Cytokines and Neuroinflammationmentioning
confidence: 99%